The extracellular β-glucosidase BGL2 has two variants with different molecular sizes and hydrolytic activities in the stipe or pilei of Coprinopsis cinerea. Issue 11 (17th November 2021) - Dai, Rujuan; Yang, Mingmei; Zhao, Jing; Liu, Xiao; Zhou, Yajun; Kang, Liqin; Zhang, Wenming; Lyu, Linna; Yuan, Sheng; Liu, Zhonghua
Abstract : Two variants of extracellular β-glucosidase (BGL2) were purified from the stipe and pilei of Coprinopsis cinerea . In the stipe, BGL2 was a monomeric protein with an apparent molecular mass of approximately 220 kDa, representing a mature full-length peptide of BGL2. However, in the pilei, the apparent molecular mass of BGL2 was only approximately 120 kDa, consisting of the 60 kDa N-terminal fragment and 55 kDa C-terminal fragment. The hydrolytic activities of BGL2 purified from the pilei were higher than those of BGL2 purified from the stipe. No mRNA splice variants of bgl2 were detected. Therefore, the different variants of BGL2 in the stipe and pilei were not formed by differential RNA splicing. Furthermore, in vitro experiments showed that full-length BGL2 could be cleaved by endogenous proteases from pilei or commercial trypsin at a similar site to form an oligomeric protein consisting of the N-terminal fragment and C-terminal fragment similar to BGL2 from pilei. The hydrolytic activity of BGL2 increased after cleavage by those proteases in vitro . We conclude that the 120 kDa variant of BGL2 in the pilei of C. cinerea is formed by posttranslational proteolytic cleavage. Posttranslational proteolytic cleavage is an efficient way to regulate the activity of BGL2 to adapt to the needs of different physiological functions in the elongation stipe and expansion pilei of C. cinerea .